Two new species of Richardina A. Milne-Edwards, 1881 (Crustacea: Decapoda: Stenopodidea: Stenopodidae), representing the first occurrences of the genus from the Pacific - Saito, Tomomi; Komatsu, Hironori (Zootaxa, 2009)
More than a century after the description of Richardina fredericii Lo Bianco, 1903, two new species of the stenopodid genus Richardina A. Milne-Edwards, 1881, are described and illustrated. Richardina ohtsukai n. sp. was collected from the Nansei Islands, southwestern Japan at depths of 655 – 730 m and R. parvioculata n. sp. was collected from off Tosa Bay, western Japan at a depth of 517 m. To our knowledge, these are the first occurrences of the genus from the Pacific and greatly extend its known geographical range, as the genus Richardina is previously known only from the Atlantic Ocean and Mediterranean Sea. Species of Richardina are very similar to each other with few morphological differences. R. ohtsukai is unique in having additional movable spines on the dorsal margins of the dactyli of the fourth and fifth pereopods. R. parvioculata is distinguished from congeners by way of its generally reduced armament of the carapace and pleon as follows: it lacks the median row of spines on the posterior margin of the cervical groove, has a relatively large eyestalk and small-sized cornea, and blunt spines on the dorsolateral carinae of the telson.